2000
DOI: 10.1097/00008571-200007000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, passive and active cigarette smoking and N-acetyltransferase 2 genotype

Abstract: The relationship of breast cancer to cigarette smoking is inconsistent in the literature, possibly due in part to heterogeneity in carcinogen metabolism. N-acetyltransferase 2 (NAT2) enzyme activity is believed to play a role in the activation of tobacco smoke carcinogens. We examined the effect of NAT2 genetic polymorphisms on risk of breast cancer from active and passive smoking. Women were recruited from those who had suspicious breast masses detected clinically and/or mammographically. Questionnaire data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 41 publications
1
30
1
Order By: Relevance
“…Population‐based studies avoid some of these limitations, but the potential for recall and selection bias must still be considered. Although the results of 7 hospital‐based26, 27, 28, 29, 30, 31, 32 and 4 screening‐based31, 33, 34, 35 studies are mixed, they generally are not inconsistent with our own findings. Only one of these studies examined smoking of 40 cigarettes/day or more28 and found a 30% increased risk among high‐intensity smokers compared to never‐smokers.…”
Section: Discussioncontrasting
confidence: 59%
“…Population‐based studies avoid some of these limitations, but the potential for recall and selection bias must still be considered. Although the results of 7 hospital‐based26, 27, 28, 29, 30, 31, 32 and 4 screening‐based31, 33, 34, 35 studies are mixed, they generally are not inconsistent with our own findings. Only one of these studies examined smoking of 40 cigarettes/day or more28 and found a 30% increased risk among high‐intensity smokers compared to never‐smokers.…”
Section: Discussioncontrasting
confidence: 59%
“…Few studies have evaluated the effect of NAT2 variants in studies of passive smoking and breast cancer. Two case control studies have suggested no modification of observed main effects for rapid vs. slow acetylators (29, 45), but a German case-control study suggested that, contrary to the observed relationship with active smoking in which slow acetylation is associated with greater risk, passive smoking was associated with higher risk in rapid acetylators (46). Although there have been some interesting, if null, studies of passive smoking and other polymorphisms (35, 47, 48) this remains a relatively uncharted area of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that women with the slow acetylation phenotypes for NAT2 may be more adversely affected by tobacco smoking (3941) but the data have been inconsistent (42–43). Our results indicate that the NAT1 rapid genotype (without NAT*10 alleles) increases the risk of NHL in smokers relative to the risk observed in non-smokers, indicating that NAT2 activation (via O-acetylation) is more important than deactivation.…”
Section: Discussionmentioning
confidence: 99%